Using The Heritage Of The Ancestors In The Formation Of Patriotism In The English Language Lessons In Students - Ibadat Khidirova Niyozalievna (Euro Asian Journal Publishing, 2024)
This article is a in pedagogical research, there are ideas about the system of patriotic education in students and approaches to the fact that the heritage of ancestors is an element of this system, didactic factors of using the heritage of ancestors in the formation of patriotism in students, and methods of educating students in the spirit of patriotism (using artistic and historical literature).
Keywords: Education; ancestry; heritage